Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M L; Lamarti, A; Abdali, A; Badoc, A (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

Influence of Growth Regulators on Shoot Proliferation in Quercus suber L. - Romano, A; Noronha, C; Martins-Loução, M a (Annals of Botany, 1992)
Procedures have been developed to standardize the multiplication stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds were established on Gresshoff and Doy basal medium containing 1 mg I−1 of 6-benzylaminopurine (BAP). Initiation of cultures was possible all over the year. The effects of BAP, Z, IBA, 1AA and NAA and various nutrient formulae on shoot growth and proliferation was investigated. BAP was more suitable than zeatin. Shoot proliferation and elongation were strongly improved by the combination BAP/IAA in the presence of low salt media, like Gresshoff and Doy or Woody Plant medium. Both rates were significantly increased when a double-phase culture system was used. Shoots have been multiplied for 1 year at the rate of three to four-fold every 4 weeks without any decline of vigour. Rooting was achieved by briefly dipping the basal ends of in vitro regenerated shoots in an IBA concentrated solution. The results here reported constitute a promising step towards large scale in vitro propagation of a species in which conventional vegetative propagation by cuttings is very difficult.
Keywords: Auxins; browning; cork-oak; cytokinins; Forestry; multiplication; Quercus suber L.; re-invigoration; re-multiplication; two-phase medium

Micropropagation of mature cork-oak (Querqus suber L.): establishment problems - Romano, A; Martins-Loução, M a (Scientia gerundensis, 1992)
Procedures have been developed to standardize the establishment stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds cultured in Gresshof and Doy (1972) (GD) medium were used as first explant. Establishment of cultures was very difficult due to browning of the tissue and/or the medium and bacterial contamination. Browning problems, probably due to phenolic compounds exudation of the primary explant, were found to be higher in winter. Nevertheless, initiation of cultures was possible all over the year, presumably due to the preconditioning of cuttings. Explants were established in a GD medium containing 6-benzlaminopurine (BAP) 1 mgl-1. Every 4 weeks the cultures were subcultured to the same GD medium and induced to proliferate being 4:1 the multiplication rate. Shoots were induced to elongate by decreasing BAP concentration. In vitro rooting on agar-solidified medium suplemented with 1 mgl-1 indolacetic acid (IAA) gave the best results. Liquid medium (sorbarod system) and in vivo rooting were also assayed.
Keywords: browning; contaminants; cork-oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture